2015
DOI: 10.1515/bjmg-2015-0008
|View full text |Cite
|
Sign up to set email alerts
|

Early Onset Marfan Syndrome: Atypical Clinical Presentation of Two Cases

Abstract: Early onset Marfan Syndrome (eoMFS) is a rare, severe form of Marfan Syndrome (MFS). The disease has a poor prognosis and most patients present with resistance to heart failure treatment during the newborn period. This report presents two cases of eoMFS with similar clinical features diagnosed in the newborn period and who died at an early age due to the complications related to the involvement of the cardiovascular system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Ozyurt et al reported two cases of early onset MFS. [7] One of these cases was a 2-month old with a clinical phenotype strikingly similar to our case. Features included arachnodactyly, pectus excavatum, similar facial features, and craniosynostosis.…”
Section: Discussionsupporting
confidence: 75%
“…Ozyurt et al reported two cases of early onset MFS. [7] One of these cases was a 2-month old with a clinical phenotype strikingly similar to our case. Features included arachnodactyly, pectus excavatum, similar facial features, and craniosynostosis.…”
Section: Discussionsupporting
confidence: 75%
“…MFS is generally an autosomal dominant disorder with variable expressivity caused by mutations in FBN1 . Approximately 75% of classic MFS cases are hereditary, while eoMFS is mainly sporadic (5). Varied changes in protein domains caused by these point mutations lead to diverse clinical phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…MFS is generally an autosomal dominant disorder with variable expressivity caused by mutations in FBN1. Approximately 75% of classic MFS cases are hereditary, while eoMFS is mainly sporadic [5]. The FBN1 mutations cause various changes in the numerous domains of the protein, which lead to diverse clinical phenotypes.…”
Section: Discussionmentioning
confidence: 99%